Ethics in Commerce Degrees â€” Why and How? - Smark, Ciorstan (Accounting Department,, 2000)
The concept of ethics education in commerce almostattracts as much cynicism as the term business ethics. ls there any place for ethics in a commerce degree? The short answer to this question from the authorsâ€™ point of view is â€œyesâ€, but one needs to think carefully about how to incorporate ethics into the commerce curriculum. This paper examines two key issues facing commerce educators. Firstly, we attempt to provide reasons why business ethics should be part of the commerce curriculum. Secondly, if ethics is to be part of the curriculum, we provide some suggestions as to how it should be incorporated.'